DATA STRUCTURES AND PROGRAM DESIGN USING PYTHON a self-teaching introduction. - Malhotra, Dheeraj; Malhotra, Neha (MERCURY LEARNING & INFORM, 2020)
Data structures provide a means to managing huge amounts of information such as large databases using SEO effectively and creating Internet/Web indexing services. This book is designed to present fundamentals of data structures for beginners using the Python programming language in a friendly self-teaching format.
Keywords: Data structures (Computer science); Python (Computer program language); elektronické knihy; electronic books